READINESS TECHNOLOGY AND SUCCESS MODEL INFORMATION TECHNOLOGY IN IMPLEMENTATION BETWEEN SMEs IN JAKARTA - Sani, Asrul; Aisyah, Siti; Budiyantara, Agus; Doharma, Rouly; Hindardjo, Anton; Frieyadie, Frieyadie (JITK (Jurnal Ilmu Pengetahuan dan Teknologi Komputer), 2022)
In general, the use of information technology plays an important role in organizational development. Similarly, if the advancement of information technology can be applied to the financial sector, small and medium enterprises, and so on, the sector's selling value will increase. This study was carried out to determine the level of readiness of the SMEs sector in carrying out information technology implementation projects in business management. In this case, the researcher is developing a research model by combining and adapting a technology readiness model and a success model in the development of information technology to the development of SMEs in Jakarta. This quantitative study included 226 SMEs workers and managers. The data was processed and analyzed using the PLS-SEM method and SmartPLS 3.0 software, with descriptive data being entered into a spreadsheet application. The study also describes the findings of the readiness factor, which has a significant impact on the success of information technology development in Jakarta SMEs